1994
DOI: 10.3109/15563659409000430
|View full text |Cite
|
Sign up to set email alerts
|

Phenthoate Metabolites in Human Poisoning

Abstract: Five metabolites were detected in the plasma and urine of a patient following ingestion of the organophosphate insecticide, phenthoate. Intact phenthoate was detected only in gastric lavage fluid. After methylation of acidic extracts of plasma and urine, phenthoate acid, demethyl phenthoate, demethyl phenthoate oxon acid, demethyl phenthoate S-isomer, and demethyl phenthoate acid S-isomer were identified with synthesized phenthoate analogues by gas chromatography and gas chromatograph-mass spectrometry. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Phenthoate is known as an organophosphate pesticide having low toxicity in humans . In a previous case of fatal phenthoate poisoning reported by Hattori et al., the phenthoate concentration in the blood was 18.5 mg/mL , which was higher than that detected in the cardiac blood in the present case; however, the postmortem blood examined in that case had not been determined to be peripheral or cardiac blood in the autopsy.…”
Section: Resultscontrasting
confidence: 64%
See 4 more Smart Citations
“…Phenthoate is known as an organophosphate pesticide having low toxicity in humans . In a previous case of fatal phenthoate poisoning reported by Hattori et al., the phenthoate concentration in the blood was 18.5 mg/mL , which was higher than that detected in the cardiac blood in the present case; however, the postmortem blood examined in that case had not been determined to be peripheral or cardiac blood in the autopsy.…”
Section: Resultscontrasting
confidence: 64%
“…In the present case, phenthoate was present in the stomach contents (4.55 g); hence, we concluded that the phenthoate had been orally ingested. Moreover, phenthoate contains a carboxyester moiety in the acidic side chain, which is hydrolyzed by carboxylesterase in the body to form a corresponding nontoxic metabolite, phenthoate acid . Ageda et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations